Law of the Jungle - La Cour, Hans; Christoffersen, Michael (Denmark : Underbjerg, Henrik ; Frost, Stefan, 2011)
In 2008, the Peruvian government divided Peru into over 100 blocks covering 70 per cent of the country. It then sold the rights to exploit the rainforest to multinational companies. In protest, a group of indigenous people decided to occupy the airfield of the oil company Pluspetrol. They wanted to let Plusptetrol know they were destroying their livelihood – for years their rivers had been full of oil, and their children had died young. When a policeman is killed, a group of the indigenous men are jailed. A week by boat from their families, they have to try to clear their names in a courtroom where everything is stacked against them – including a corrupt police force. Their only hope is an impassioned defense lawyer – and an eyewitness too frightened to testify. With extraordinary access to the judicial process, we follow their plight.
Verzio Film Festival Submission
With voice-over in Hungarian
Verzio Film Festival Submission
Keywords: Documentary films